Fresno County Bar Associations' 105th Annual Bar Banquet - Watkins, Howard::::::::: (1987)
Howard Watkins holding his Fresno County Bar Association gift of an 18-200mm Canon camera lens This was Howard's first wide angle to telephoto zoom lens